Analysis and Handling of Waste in Companies Implementing Lean at a Beginner Level: Analisa dan Penanganan Pemborosan Bagi Perusahaan Dalam Penerapan Lean Tingkat Pemula - Aditia Shofyan, Rizal; Karningsih, Putu Dana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The manufacturing sector, particularly in consumer goods, faces constant pressure to enhance efficiency and reduce waste. Specific Background: A Surabaya-based mosquito coil manufacturer has adopted automation in its production processes; however, inefficiencies persist due to various non-value-adding activities. Knowledge Gap: Although lean manufacturing offers promising solutions, practical integration of its tools remains a challenge, especially for companies at the early stage of implementation. Aims: This study aims to systematically identify and eliminate waste by applying a lean manufacturing framework that integrates Process Activity Mapping (PAM), Gemba Shikumi, the 5 Whys analysis, and the Lean Assessment Matrix. Results: Thirteen types of wasteful activities were identified, with five categorized as critical through Gemba Shikumi. Root cause analysis using the 5 Whys generated several improvement alternatives, which were prioritized using the Lean Matrix. The top three recommendations were selected for implementation. Novelty: The integration of multiple lean tools into a phased and context-sensitive framework represents a practical innovation for early-stage lean adoption. Implications: The results offer a structured approach for similar manufacturing firms to improve productivity by effectively identifying and addressing wasteful activities. Highlights: Identifies 13 wasteful activities using integrated lean tools. Prioritizes actions with Lean Matrix for practical implementation. Offers a framework tailored for early lean adoption stages. Keywords: Lean Manufacturing, Waste Elimination, Process Activity Mapping, Gemba Shikumi, 5 Whys Analysis